STRATEGIES AND CHALLENGES IN PREVENTING STUDENT AND YOUTH BRAWLS AS A CRIMINAL ACT: AN ISLAMIC LAW PERSPECTIVE - Hamzah Hasan; Fadhliah Mubakkirah; Nurul Lutfiah Sultan; Haeni Mukti; Arfah (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2026)
The phenomenon of student and youth brawls represents a recurring form of collective violence with serious implications for personal safety, public order, and social stability. This article analyzes strategies and challenges in preventing student and youth brawls as criminal acts from an Islamic legal perspective, employing a normative-juridical and socio-legal approach grounded in uṣūl al-fiqh principles. The findings reveal that student and youth brawls constitute acts fundamentally contrary to the primary objectives of Islamic law (maqāṣid al-sharīʿah) and are therefore subject to prevention under several fiqh principles. From an uṣūl al-fiqh standpoint, the prevention of student and youth brawls must be understood not merely as a reactive response to consequences, but as a proactive effort to eliminate potential harm through a systematic preventive framework. Nevertheless, effective implementation remains hindered by several persistent challenges, including the normalization of a culture of violence among adolescents, the pervasive influence of digital media, weakened social control mechanisms, and the growing gap between Islamic legal norms and contemporary social realities. This article argues that synergy among Sharia values, state policy, and active community participation constitutes a fundamental prerequisite for effective student and youth brawls prevention in modern society.